2007
DOI: 10.1103/physrevb.75.165410
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the surface bands along theX¯M¯line of the Cu(100) surface

Abstract: Recent semiempirical linear combination of atomic orbital method ͑LCAO͒ calculations for the Cu surfaces of low Miller indices have given surface bands which agree very well with the available experimental data. These calculations indicate the existence of various surface states and resonances, in particular, in the s-d band region, which have not yet been experimentally observed. We have checked a part of these predictions by performing angle-resolved photoemission measurements along the X -M direction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The Cu(100) is characterized by two intense bulk projected states. 33,34 Upon Bi deposition, four Bi-induced peaks arise, namely E 2 , E 3 , E 4 , and E 5 , at 1.74 eV, 1.69 eV, 1.19 eV, and 0.97 eV of binding energy, respectively . These Bi-induced features are intense if excited by light polarized in the surface plane.…”
Section: Resultsmentioning
confidence: 99%
“…The Cu(100) is characterized by two intense bulk projected states. 33,34 Upon Bi deposition, four Bi-induced peaks arise, namely E 2 , E 3 , E 4 , and E 5 , at 1.74 eV, 1.69 eV, 1.19 eV, and 0.97 eV of binding energy, respectively . These Bi-induced features are intense if excited by light polarized in the surface plane.…”
Section: Resultsmentioning
confidence: 99%
“…In this letter we present the results of density functional theory (DFT) calculations on the p(2×4) glycinate monolayer and show that the origin of the anisotropic free-electron-like state (AFES) is a Cu Shockley surface state (SS). Although Kanazawa et al did not observe a SS near the Fermi energy on the bare Cu (100) surface [1] a SS has been identified near the Fermi energy at the surface Brillouin zone (SBZ) boundary [4,5,6,7]. We show that the SS is folded back to the Γ point in the (SBZ) for the p(2×4) structure studied by Kanazawa et al, and that the anisotropic parabolic dispersion of the observed AFES is due to enhanced tunneling into the SS, mediated by the lowest unoccupied molecular orbitals of the glycinate ions.…”
mentioning
confidence: 96%
“…In this communication we present the results of density functional theory (DFT) calculations on the p(2 × 4) glycinate monolayer and show that the origin of the AFES is a copper Shockley surface state (SS). Although Kanazawa et al did not observe a SS near the Fermi energy on the bare Cu(100) surface [5] a SS has been identified near the Fermi energy at the surface Brillouin zone (SBZ) boundary [6][7][8][9]. We show that the observation of a AFES is due to enhanced tunnelling into the SS, mediated by the lowest unoccupied molecular orbitals of the glycinate ions and by the backfolding of the SS to the ¯ point in the SBZ for the p(2 × 4) structure.…”
mentioning
confidence: 96%